Culturally Responsive Mathematics Teaching Implications for Teacher Preparation and Professional Development - Gupta, Charu (JOURNAL OF INDIAN EDUCATION, 2017)
School mathematics is often conceptualised as being neutral, decontextualised and culture-free. In consonance with reforms in mathematics education, the National Curriculum Framework (NCF)–2005 envisages a new vision of school mathematics that connects mathematical knowledge and social worlds of children. This epistemological shift places new and challenging demands on teachers and teacher-educators. Challenging the ‘deficit theory’, the paper acknowledges home, community and culture-based practices as reservoirs of knowledge, which need to be strategically tapped in classrooms. The paper, in this light, discusses the possible ways in which a teacher and teacher-educators can collaborate to address one’s sociocultural beliefs and assumptions about knowledge and learners in mathematics classrooms, and develop cultural awareness and responsiveness. Most importantly, the paper argues for a deeper engagement with equity and justice issues in mathematics teacher education.